The impact of previous cancer on overall survival of bladder cancer patients and the establishment of nomogram for overall survival prediction. Issue 38 (18th September 2020) - Wang, Zhengquan; Zhou, Yuan; Guan, Chao; Ding, Yinman; Tao, Sha; Huang, Xiaoqi; Chen, Liang; Zhang, Fei; Zhang, Rentao
Abstract : Abstract: To investigate the role of previous cancer on overall survival in patients with bladder cancer (BCa) and to establish an effective prognostic tool for individualized overall survival prediction. A total of 78, 660 patients diagnosed with BCa between 2000 and 2013 were selected from the Surveillance, Epidemiology, and End Results (SEER) database, among which 8915 patients had a history of other cancers. We compared the overall survival between patients with and without previous cancer after propensity score matching and we further established a nomogram for overall survival prediction. Univariate and multivariate Cox analyses were used to determine independent prognostic factors. The calibration curve and concordance index (C-index) were used to assess the accuracy of the nomogram. Cox proportional hazards models and Kaplan–Meier analysis were used to compare survival outcomes. BCa patients with previous cancer had worse overall survival compared with those without previous cancer (HR = 1.37; 95%CI = 1.32–1.42, P  < .001). Cancers in lung prior to BCa had the most adverse impact on overall survival (HR = 2.35; 95%CI = 2.10–2.63; P  < .001), and the minimal impact was located in prostate (HR = 1.16; 95%CI = 1.10–1.22; P  < .001) for male and in gynecological (HR = 1.15; 95%CI = 1.02–1.30; P   =  .027) for female. The shorter interval time between 2 cancers and the higher stage of the previous cancer development, the higher risk of death. Age, race, sex, marital status, surgery, radiation, grade, stage, type of previous cancer as the independent prognostic factors were selected into the nomogram. The favorable calibration curve and C-index value (0.784, 95%CI = 0.782–0.786) indicated the nomogram could accurately predict the 1-, 3-, and 5-year overall survival rate of BCa patients. Previous cancer has a negative impact on the overall survival of BCa patients and requires more effective clinical management. The nomogram provides accurate survival prediction for BCa patients and might be helpful for clinical treatment selection and follow-up strategy adjustment.